Standardizing interaction design education - Thomassen, Aukje; Ozcan, Oguzhan (PERGAMON-ELSEVIER SCIENCE LTD, 2010)
The objective of this paper is to which extend the didactic format of studio-based group-work is applicable for creating a common-ground for Interaction Design Education in European Perspective. The current debate on design education shows us a landscape of different initiatives. So far difficulties have arisen in the area of accreditation and validation of interaction design as an educational field. This in contrast to all the EU agreements and strategies. In this paper we will closely look at these difficulties from the perspective of the intensive EU-funded summer-course on Interaction Design with four participating institutes coming from four different EU countries. The course facilitated learning through the usage of the didactic format of studio-based group-work. This approach enabled blended learning and provided a commongroud for intercultural learning through design. A qualitative assessment conducted on the learning format by the 40 multi-cultural group of students and staff provided insightful guidelines into the appreciation and value of the format. The evaluation results showed that the studio-based group-work is an efficient method to overcome cultural differences in design methodology, teamwork and personal skills. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Cross-cultural products; Learning communities; Media in education; Teaching/learning strategies; Computer Science; Education & Educational Research